Departing from the mutual exclusiveness of strength and ductility in nanocrystalline metals with vacancy induced plasticity. (December 2018) - Islam, Zahabul; Wang, Baoming; Hattar, Khalid; Gao, Huajian; Haque, Aman
Abstract: Strength and ductility are mutually exclusive in metallic materials. To break this relationship, we start with nanocrystalline Zirconium with very high strength and low ductility. We then ion irradiate the specimens to introduce vacancies, which promote diffusional plasticity without reducing strength. Mechanical tests inside the Transmission Electron Microscope reveal about 300% increase in plastic strain after self ion-irradiation. Molecular dynamics simulation showed that 4.3% increase in vacancies near the grain boundaries can result in about 60% increase in plastic strain. Both experimental and computational results support our hypothesis that vacancies may enhance plasticity through higher atomic diffusivity at the grain boundaries. Graphical abstract: Unlabelled Image